Relayout Area Divisi Oven dengan Metode Systematic Layout Planning (SLP) PT. XYZ - Gunawan, Akilla Alfrets Deanoffa; Handy Febri Satoto (SURYA TEKNIKA, 2024)
PT. XYZ is a manufacturing company engaged in the production of notebooks and chemicals. This study aims to improve production efficiency in the oven division of PT. XYZ, especially on the SS-29 oven machine, by implementing the Lean Manufacturing and Systematic Layout Planning (SLP) methods. This study begins with an analysis of initial conditions that show various wastes, including excess material transfer, waiting time, and inefficient operator movements. The SLP approach is used to analyze the initial layout and design alternative new layouts by considering the results of the Activity Relationship Chart (ARC) and space requirements. Lean Manufacturing functions to identify and reduce activities that do not provide added value in the production process. The results of implementing the new layout show a reduction in material transfer distance by 41.12%, which has a direct impact on time and energy efficiency. In addition, production cycle time is significantly reduced, increasing operator productivity. This new layout also reduces waste in terms of waiting and transportation, while supporting a more responsive workflow. As a recommendation, PT. XYZ needs to immediately implement a new layout by considering implementation costs and impacts on ongoing operations. Continuous adjustment of the layout is also recommended to ensure the solution remains relevant, as well as to serve as a basis for further research in evaluating long-term impact and implementation in other divisions.